Architectural Documentation Through Thick Description - Akboy-Ilk, Serra (Enquiry The ARCC Journal for Architectural Research, 2016)
Architectural documentation focuses on deconstructing the built environment in the form of two-dimensional measured drawings. Documentation activities, therefore, seem to be purely technical exercises that afford documenters the ability to collect metric data from architectural surfaces and then to transform field data into graphical representations. However, architectural documentation involves more than just the technical reproduction of a context as it involves an intellectual effort to thickly describe the socio-cultural heritage setting. During the process, documenters conduct an informed survey and bring all the knowledge with them in order to decode the cultural signifiers embedded in the architectural heritage. Discussing measured drawings as an interpretive account of the built environment and surveying practices as a means to acquire heritage information, this article examines architectural documentation through the lens of thick description.